Do university-educated immigrants recover economically from a slow start? - Garnett Picot; Feng Hou; Eden Crossman (Economic and Social Reports)
The selection of highly educated immigrants is based in part on the premise that they can better adapt to the labour market and will have, on average, better economic outcomes than less-educated immigrants. Earlier research indicates that this is the case. However, some university-educated immigrants have a slow start in the initial years after immigration. Little Canadian research has considered whether these immigrants eventually catch up with similarly educated immigrants who have early economic success. Likewise, it is unknown whether they outperform less-educated immigrants. Using the Longitudinal Immigration Database, this study looks at the long-term economic outcomes of university-educated economic principal applicant immigrants who immigrated at the ages of 20 to 44 during the period from 1990 to 2014 by their earnings level in the initial years after immigration.